(untitled) (Nuntius Antiquus, 2013)
This paper aims to explore the onset and peak of the development of Gothic architecture, religious art and architecture eminently urban, between the twelfth and thirteenth centuries in the medieval West, in a socio-religious Catholic hegemony. The message sent to the faithful through the Gothic architecture, replacing Romanesque, indicates in this case a major change in mindset, since we consider the importance of semiotics in art, architecture and urban space.